[OP.1C.01] HIGH SALT DIET INCREASES AORTIC STIFFNESS AND PRESSURE PULSE AMPLIFICATION IN RAT. (September 2016) - Butlin, M.; Connolly, K.; Spronck, B.; Georgevsky, D.; Mceneiry, C.; Wilkinson, I.; Avolio, A.
Abstract : Objective: High salt consumption is associated with increased blood pressure and vascular changes in humans. This association is confounded by other lifestyle factors that could equally influence cardiovascular function. This study examines effects of high salt diet on aortic function in a controlled animal study. Design and method: Sprague-Dawley rats were fed either high salt (8% sodium chloride, n = 6) or normal chow (0.26% sodium chloride, n = 5) from weaning. Body weight (BW), nose-to-rump length, tail-cuff systolic blood pressure (SBP), water and food intake, and urine output were measured. At 14 to 17 weeks, rats were anaesthetised and thoracic and abdominal aortic pressure (invasive solid-state catheters) recorded over a physiological mean arterial pressure (MAP) range (60 to 150 mmHg, induced via intra-venous infusion of phenylephrine and sodium nitroprusside, 30 μg/kg/min). Aortic pulse wave velocity (aPWV) and thoracic to abdominal aortic pulse pressure amplification (PPA) were calculated. Left ventricular (LV) and kidney mass were recorded post-mortem. Results Results: High salt diet rats had lower BW (average across all age: 451 ± 57 g, control 498 ± 68 g, p = 0.03), body mass index (0.79 ± 0.08 g/cm2, control 0.82 ± 0.10 g/cm2, p < 0.001) and kidney mass (kidney/BW 0.50 ± 0.09%, control 0.39 ± 0.05%, p = 0.01) without LV hypertrophy (LV/BW 0.24 ± 0.04%, control 0.22 ± 0.03%, p = 0.16). Food intake was similar (high salt 20 ± 3 g/day, control 19 ± 5 g/day, p = 0.36). High salt diet rats drank more (65 ± 10 ml/day, control 22 ± 6 ml/day, p < 0.001) with correspondingly higher urine output (55 ± 9 ml/day, control 15 ± 6 ml/day p < 0.001); conscious SBP was greater (125 ± 12 mmHg, control 117 ± 13 mmHg, p < 0.05). High salt diet resulted in higher aPWV (high salt aPWV across MAP range 60 to 150 mmHg, 4.3 ± 0.2 to 5.4 ± 0.2 m/s, control 3.6 ± 0.3 to 3.9 ± 1.1 m/s, p < 0.001 at each 5 mmHg MAP interval). PPA was greater in high salt diet rats (high salt PPA across MAP range 60 to 150 mmHg, 0.78 ± 0.04 to 1.53 ± 0.27, control 0.62 ± 0.14 to 1.25 ± 0.17, p < 0.001 at each 5 mmHg MAP interval). Conclusions: A high salt diet induced moderately higher arterial blood pressure, greater aortic stiffness and higher PPA, indicating marked changes in transmission characteristics of the aorta, including altered stiffness gradient across the aorta and changed peripheral wave reflection characteristics.